The Effects of Farmyard Manure and Green Manure Applications on Some Soil Physical Properties - Metin MÜJDECİ; Azra Cevahir DEMİRCİOĞLU; Pelin ALABOZ (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
In this research was carried out to determine the effects of farmyard manure and green manure applications on some soil physical properties in a three yearly organic vegetable cultivation field. The effects of control (C), farmyard manure (FYM) (35 t ha-1) and green manure (GM) applications on some soil physical properties (soil water characteristics (0.001, 0.1, 0.33, 1, 5, 10 and 15 bars), available water content, porosity and bulk density) were investigated in 0-10 and 10-20 cm soil depths for two years. At all tension values, the highest volumetric soil water contents were obtained for FYM application and the lowest ones for C treatment. The highest total porosity along with macro and micro porosity were found in the FYM application and the lowest ones were found in the C application. The available water content was the highest in the GM application and the lowest in the C application. In addition, the highest bulk density was found in C application and the lowest bulk density was found in FYM application. These results showed that the effects of different organic material applications on soil physical properties are important.